Self-Efficacy of Teachers in Initial Training: A Comparison between the Populations of Two Universities - Chaves-Barboza, Eduardo (2019)
This article carries out a comparison of the self-efficacy of teachers in initial training, between the populations of two universities. A questionnaire with two Likert scales is applied in two samples, 836 subjects from the Universidad Nacional (Costa Rica) and 588 from the Universidad de Granada (Spain). The data is reviewed by means of descriptive and inferential statistics (95% confidence interval), correlation tests (Kendall τ correlation coefficient) and variance analysis (Mann–Whitney U test and Kruskal–Wallis H test). The results indicate that both populations show high levels of self-efficiency during their initial training, where the self-perceived capacity to pay attention to the explanations and instructions of the teachers excels. Meaningful differences are observed with getting ahead with difficult situations, doing the extra-class tasks and having motivation in the less interesting class.